1985
DOI: 10.1016/s0140-1971(85)80007-5
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem, ethnic identity, and behavioral adjustment among Anglo and Chicano adolescents in West Texas

Abstract: This study provides a comparison of similarities and differences with respect to ethnic identity between Anglo and Chicano adolescents from Texas. A path analysis model was used to test a theoretical assumption concerning proposed antecedents and consequences of self‐esteem. Research instruments included the Rosenberg Self Esteem Scale, the Semantic Differential (scales for Myself and My Ethnic Group) and the McGuire White Measure of Social Status. Results were consistent with the interpretation that there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 4 publications
2
41
0
1
Order By: Relevance
“…Not only was mediation found for the Turkish, Moroccan and Surinamese early adolescents; it was also found among their Dutch peers. This suggests that minority status does not have a moderating effect on how negative ethnic peer interactions influence global self-worth and how ethnic self-esteem is implicated in this process (see also Grossman, Wirt, & Davids, 1985;Verkuyten & Lay, 1999). This result suggests a "one model fits all" approach to studying early adolescents in multiethnic settings and is in agreement with multifaceted or hierarchical models of the self.…”
Section: Discussionmentioning
confidence: 80%
“…Not only was mediation found for the Turkish, Moroccan and Surinamese early adolescents; it was also found among their Dutch peers. This suggests that minority status does not have a moderating effect on how negative ethnic peer interactions influence global self-worth and how ethnic self-esteem is implicated in this process (see also Grossman, Wirt, & Davids, 1985;Verkuyten & Lay, 1999). This result suggests a "one model fits all" approach to studying early adolescents in multiethnic settings and is in agreement with multifaceted or hierarchical models of the self.…”
Section: Discussionmentioning
confidence: 80%
“…A positive racial or ethnic identity has been found to be associated with more favorable scores on indices of adjustment in several studies of older adolescents and adults (Bates, Beauvais, & Trimble, 1997;Brook, Whiteman, Balka, Win, & Gursen, 1998;Grossman, Wirt, & Davids, 1985;Munford, 1994;Pyant & Yanico, 1991;Rotheram-Borus, 1990;Zimmerman, Ramirez, Washienko, Walter, & Dyer, 1998). Paralleling research in the stress area, it is less clear whether racial or ethnic identity retains a similar protective function at earlier stages of development.…”
Section: Identity and Self-esteemmentioning
confidence: 99%
“…Group identification provides individuals with a social and psychological 'place' within which they can establish a sense of meaning and identity (Simon, 1999;Spears, Jetten, & Scheepers, 2002). Minority group identification is correlated with psychological adjustment among a number of different kinds of stigmatized groups (Bat-Chava, 1994;Grossman, Wirt, & Davids, 1985;Munford, 1994;Phinney, 1990;Rowley, Sellers, Chavous, & Smith, 1998), and experimental work has found that the mere presence of similarly stigmatized others raises self-esteem and lowers depression and anxiety (Frable, Pratt, & Hoey, 1998;McKenna & Bargh, 1998). Furthermore, regardless of the ingroup's status, identification with ingroup social categories is associated with positive well-being (Branscombe & Wann, 1991).…”
Section: The Psychological Costs Of Exclusionmentioning
confidence: 99%